Analysis of the Reaction of G-20 Countries' Stock Markets to the Russia Ukraine War - Fatika Apta Calista; Hendro Lukman (PT Publikasiku Academic Solution, 2026)
The Russia–Ukraine War, which began on February 24, 2022, triggered global economic disruptions and potentially affected the capital markets of G-20 member countries. This study aims to analyze stock market reactions across G-20 countries using an event study method. The research data consist of stock market indices from 19 G-20 economies, observed over a five-day window before and a five-day window after the event. The Wilcoxon signed-rank test was used for hypothesis testing. The results show that six countries—France, Germany, Italy, Australia, India, and the European Union (EU)—experienced significant negative reactions, while the remaining thirteen countries showed no statistically significant differences. This study concludes that the impact of the war on G-20 capital markets is heterogeneous across markets. Therefore, investors should consider country-specific characteristics when developing international portfolio diversification strategies.